2011
DOI: 10.1039/c1em10120j
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate leaching to shallow groundwater systems from agricultural fields with different management practices

Abstract: Monitoring the concentration of NO(3)-N from agricultural fields to the subsurface and shallow ground water resources have received considerable interest worldwide, since agriculture has been identified as a major source of nitrate-nitrogen (NO(3)-N) pollution of groundwater systems in intensively farmed watersheds. A study was conducted to quantify the impact of two tillage practices viz. chisel plow (CP) and no till (NT) with liquid swine manure application on nitrate leaching to the shallow ground water sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…A more likely explanation for decreased NO 3 concentrations is increased denitrification in soils under reduced tillage (Mkhabela et al, 2008;Melero et al, 2011;Tatti et al, 2015;García et al, 2016). This is perhaps due to increased organic matter, increased moisture, and decreased O 2 availability in soils, conditions that enhance denitrification rates and thus reduce leaching of NO 3 to shallow groundwater (Rekha et al, 2011). Whatever the mechanism(s) accounting for the acceleration of NO 3 declines in our streams, they agree generally with trends in the Maumee River in the Lake Erie watershed, where NO 3 concentrations actually increased between 1980 and 1990, when conservation tillage increased, but then declined rapidly over the next ~20 yr when the use of conservation tillage was common but stable (Stow et al, 2015).…”
Section: Discussionsupporting
confidence: 74%
“…A more likely explanation for decreased NO 3 concentrations is increased denitrification in soils under reduced tillage (Mkhabela et al, 2008;Melero et al, 2011;Tatti et al, 2015;García et al, 2016). This is perhaps due to increased organic matter, increased moisture, and decreased O 2 availability in soils, conditions that enhance denitrification rates and thus reduce leaching of NO 3 to shallow groundwater (Rekha et al, 2011). Whatever the mechanism(s) accounting for the acceleration of NO 3 declines in our streams, they agree generally with trends in the Maumee River in the Lake Erie watershed, where NO 3 concentrations actually increased between 1980 and 1990, when conservation tillage increased, but then declined rapidly over the next ~20 yr when the use of conservation tillage was common but stable (Stow et al, 2015).…”
Section: Discussionsupporting
confidence: 74%
“…Some studies comparing chisel plowing to no-till (NT) found little to no difference in NO 3 -N leaching (Fox, Zhu, Toth, Jemison, & Jabro, 2001;Logan, Eckert, & Beak, 1994). Other research found lower NO 3 -N concentrations in subsurface drainage from NT compared with other tillage systems with similar cropping rotations (Angle, Gross, Hill, & McIntosh, 1993;Kanwar, Colvin, & Karlen, 1997;Rekha, Kanwar, Nayak, Hoang, & Pederson, 2011). A central Iowa study showed significantly lower seasonal and annual NO 3 -N concentrations and overall N losses with NT compared with a chisel plowed treatment (Waring, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of leaching, the risk period for slurry application was autumn, which is well documented (e.g. Nila Rekha et al ., ). However, there was little risk from FYM applications made in this period, probably related to its relatively low NH 4 –N content (Table ); Sørensen & Rubæk () noted that FYM could present a leaching risk when applied in autumn if the NH 4 –N content was high.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have identified best management practices for decreasing N leaching from manure applications. Timing of application seems to be critical, with N leaching losses greater from autumn than from spring applications of liquid pig manure (Nila Rekha et al ., ). Beckwith et al .…”
Section: Introductionmentioning
confidence: 97%